Analysis on the effect of the upper wall opening on the natural ventilation performance in building / Aziz Faiz Shahir - Shahir, Aziz Faiz (2018)
Wind-driven natural ventilation has been known as an effective passive design alternative to active ventilation system towards development of sustainable buildings. This free source of energy needs to be fully utilized by people where it can be accommodated to minimize energy consumption in which cost comes from the process of cooling using electrical device such as air conditioning unit and exhaust fans.